2017
DOI: 10.22571/actabra13201755
|View full text |Cite
|
Sign up to set email alerts
|

Teste de micronúcleos em peixes e parâmetros físico-químicos da água da represa Cocais, Minas Gerais

Abstract: ResumoOs bioindicadores são usados para avaliar mudanças no ambiente aquático. Substâncias químicas incorporadas em ambientes naturais interferem no desenvolvimento desses organismos. A pesquisa teve como objetivo avaliar a qualidade da água da represa Cocais, em Patrocínio, Minas Gerais, utilizando parâmetros físico-químico da água e teste de micronúcleo em peixes. Nesse estudo, foram utilizados peixes da espécie Oreochromis niloticus L. (Tilápia-do-nilo) introduzidos na represa após a sua construção. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
3
2
0
4
Order By: Relevance
“…The numbers of micronuclei and morphological nuclear alterations found in both Barcarena and Vigia were similar to the ndings ofRocha et al (2016), who also used P. squamosissimus as a bioindicator in the Marajó Archipelago of northern Brazil, although the values were much higher than those recorded in the Nile tilapia, Oreochromis niloticus (Cichlidae), byBueno et al (2017) from a reservoir in southeastern Brazil during both the dry and rainy seasons Goes et al (2016). used the yellow n river pellona, Pellona avipinnis (Pristigasteridae), as a bioindicator at three points on the Tapajós River (in Brazilian Amazonia) and, based on the results of the micronucleus test, concluded that pollutants in the river provoked genetic alterations, based on the large quantity of micronuclei found in the cells.…”
supporting
confidence: 82%
“…The numbers of micronuclei and morphological nuclear alterations found in both Barcarena and Vigia were similar to the ndings ofRocha et al (2016), who also used P. squamosissimus as a bioindicator in the Marajó Archipelago of northern Brazil, although the values were much higher than those recorded in the Nile tilapia, Oreochromis niloticus (Cichlidae), byBueno et al (2017) from a reservoir in southeastern Brazil during both the dry and rainy seasons Goes et al (2016). used the yellow n river pellona, Pellona avipinnis (Pristigasteridae), as a bioindicator at three points on the Tapajós River (in Brazilian Amazonia) and, based on the results of the micronucleus test, concluded that pollutants in the river provoked genetic alterations, based on the large quantity of micronuclei found in the cells.…”
supporting
confidence: 82%
“…Essa alteração resulta de distúrbios circulatórios devido à condição de fluxo de fluido sanguíneo (BERNET et al, 1999). Ademais, o micronúcleo é uma lesão nuclear que pode sugerir que a exposição a genotóxicos está causando modificando geneticamente os peixes (BUENO et al, 2017).…”
Section: Discussionunclassified
“…Fish have been used as environmental biomonitor in a number of genotoxic studies (Grisólia and Cordeiro 2000;Souto 2004;Arias et al 2007;Costa et al 2008;Delunardo et al 2013;Carrola et al 2014;Lima et al 2015a, b;Rocha et al 2016;Bueno et al 2017;Hussain et al 2018;AnvariFar et al 2018;Delunardo et al 2020;Santana et al 2020). These vertebrates are appropriate models for this type of research due to their capacity for the metabolization and accumulation of pollutants that also pose a risk to humans (Ranzani-Paiva et al 2013;Ventura et al 2015;Lima et al 2015a, b).…”
Section: Discussionmentioning
confidence: 99%